Substratos alternativos e fertilizantes de liberação controlada na produção de mudas clonais de Coffea arabica L. - Torres, Luciane Gonçalves (2021)
The use of vegetative propagation by cuttings for the production of Coffea arabica L. seedlings is an alternative for the production of seedlings on a commercial scale, as well as for breeding programs for the use of F1 hybrids, ensuring the maintenance of standard genetic gain in selection, Thus, the number of selection cycles to obtain inbred lines. In order to optimize the process of obtaining clonal seedlings, the objective of this work was to evaluate the feasibility of using different substrates associated with the nutrient by means of controlled release fertilizer in the development of Coffea arabica L. disconnect seedlings by stem cutting. The experiment was installed in a randomized block design with three replications, seven cuttings per plot and 15 treatments in a 5 x 3 factorial scheme, consisting of five mixtures of substrates, as follows: commercial substrate (SC) (100%); and 1:1 proportions of carbonized coffee husk + SC, carbonized rice husk + SC, tanned coffee husk + SC, sand + vermiculite + SC) and three doses of Osmocote Plus® controlled-release fertilizer (7.5, 12, 5 and 17.5 g L-1). Adult plants of the cultivar Mundo Novo were selected from received crops and stem cuttings with five lengths each were removed. After 150 days of installation of the experiment, morphological characters related to the development of the aerial part and root system were obtained. The results were uncovered by an analysis of variance and, when tested, by testing Tukey's means. There was no interaction between the substrate and a dose of controlled-release fertilizer used for any variable under study, so the indicators were studied and the behavior of the variables within each factor level was observed. The partial replacement of the commercial substrate used for the production of seedlings by alternative materials, such as tanned/carbonized coffee husk, sand+vermiculite or carbonized rice husk is a viable alternative for the production of Arabica coffee seedlings through cuttings for better promotion of characters related to the root system. Controlled release fertilizers interfere with the development of characters related to the development of the shoots.